Pharm logical Application of Click Chemistry: A review - Rana I. Faeq1 Yusra J.Ahmed1 Sarab M. Alazawi*1 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The 1,2 ,3-triazole moiety is an important biomolecule produce by the click reaction. Copper, ruthenium1 catalyzedazide/alkyne cycloáddition pathway, click reaction is resulted of five membered rings. In order to be utilized as anticáncer, antimicrobial, antituberculosis, antiviral, anti-diabetic, antimalarial, anti-leishmanial and neuroprötective agents and also in fluorescent technology, biological targets required a method bearing the linker feature of 111,2,33-triazles and a new type of 1,2,Ӡ-triazolely including crosses with its conjugates. This review summarizes progresses over the last few years in application of 1, 2, 3-triazole derivatives and its utilities as a biomolecule. Researchers in organic fields, medicinal chemistry, photochemistry, and pharmacology will advantage from this study. This review offers important knowledge which attentive to readers.